Chitosan and hydroxyapatite scaffolds with amoxicillin for bone repair (Research, Society and Development, 2021)
The bone repair process, among other physiological mechanisms, occurs in a harmonious manner throughout the body. However, the presence of some deleterious factors such as surgery, trauma or pathology, can interfere with the physiology of bone remodeling. It´s Known that the synergistic antimicrobial action between drugs and biomaterials can help and favor osteogenesis after grafting surgery. Therefore, this study aims to develop chitosan / hydroxyapatite scaffolds with amoxicillin for bone repair in the oral cavity. For this, raw materials were selected and characterized and scaffolds were made by the processes of solubilization, dispersion and lyophilization. The characterizations were made by optical microscopy, scanning electron microscopy, eenergy dispersive spectrometer, swelling potential, degradation analysis, apparent porosity test and in vitro cell cytotoxicity. The scaffolds produced in this research showed to have not only adequate physical characteristics but also chemical and biological ones. It was as well as detected a reproducible methodology that resulted in a biomaterial with morphology that provided a high degree of swelling, porosity, satisfactory degradation and the presence of amoxicillin which was confirmed by the eenergy dispersive spectrometer. Nevertheless, the scaffolds with 30% hydroxyapatite showed the best results for in vitro cell viability. So, it is possible to conclude that the scaffolds produced show successful characteristics for bone repair in the oral cavity.